Influence of integration on development of subjects of the agrarian sector of economy - Igor Kutsenko (Agricultural and Resource Economics, 2018)
Purpose. The purpose of article is to characterize theoretical aspects of development of integration processes in agricultural sector and the integrated agrarian formations; to reveal individual factors of influence on integration processes and to review the multivector diffusion which is formed in process of creation of vertically integrated structure; to explore the main advantages and disadvantages of the integrated structure of holding type. Methodology / method / approach. The research of theoretical principles of integration processes development and their organizational forms gave the chance to substantiate scientific and practical positions concerning content and role of this phenomenon for subjects of the agrarian sector of economy. In process of writing article such methods are used: logical generalization – for theoretical justification of integration essence, integrated agrarian formations and agroholdings; the system analysis – for research and justification of multivector diffusion emergence in process of integration into structure of holding type. Results. The essence and approaches to understanding of integration as social and economic phenomenon in the agrarian sector of economy are determined. It is reasoned that vertical integration into agro-industrial structures of holding type are the most successful organizational forms for today. But at the same time it is reasoned that there is quite large number of unresolved issues concerning activity of such holding structures, the main of them are institutional unresolvations concerning property and institutional traps. It is proved that in process of integration of agricultural enterprises as participants of agroholdings, there is multivector diffusion by means of which there are internal organizational and administrative and production transformations of the participant of integration. Originality / scientific novelty. The attempt to investigate influence of the most widespread integrated formation – agrarian holding on its participants (the agricultural enterprises of different forms of ownership) and also to determine negative aspects of vertical integration and possible ways of their overcoming are made. Practical value / significance. The motivational component of the integration of agricultural enterprises into agro-industrial holding structures (agroholdings) is determined. The scheme of multivector diffusion in process of integration into structure of holding type is developed and the influence on its participants is determined. The list of negative aspects of vertical integration into agroindustrial complex is offered and the ways of their overcoming are determined.